Newborn with Vein of Galen Malformation and Concurrent Cardiac Malformation - Ávlia-Guerra, Mauricio; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2016)
Vein of Galen Aneurysmal Malformations (VGAM) is a rare malformation with a prevalence estimated at less than one in 25,000 live births. This malformation can cause high morbidity and mortality in neonates and less frequently in older children. Is a complex vascular malformation of the choroid, in the roof of the third ventricle, in the region of the velum interpositum. It is presented as an arteriovenous fistula, usually between the choroidal arteries and the aneurysm sac, leading to a dilated vein of Galen. When infants are symptomatic, the usual clinical presentation of heart failure VGAM is high output, which has been reported in up to 94 % of infants who are diagnosed with a VGAM. In the past, such failure rapidly progressed to multiorgan failure and death, with mortality reported up to 100 %, but now advances in endovascular techniques and intensive care units have improved the poor prognosis of VGAM.